Advances in pharmacology. - August, J. Thomas (Advances in pharmacology (San Diego, Calif.) ;, 1998)
Each volume of Advances in Pharmacology provides a rich collection of reviews on timely topics. Emphasis is placed on the molecular bases of drug action, both applied and experimental.